The study of development the composition of the combination vaginal gel with hop extract - M. L. Bavykina; L. I. Vyshnevska; V. A. Megalinskyi; N. M. Kosyachenko (Zaporozhye State Medical University, 2015)
Introduction. The problem of infectious and inflammatory diseases' treatment in gynecology still remains open. As the result of analysis of the domestic market of drugs for infectious and inflammatory diseases' treatment in gynecology, the insufficiency of herbal drugs with local action for this pathology treatment has been identified. The Aim is composition justification of the combined plant-based drug of local action, with anti-inflammatory, antimicrobial, estrogenic, and reparative activities for complex therapy of vaginitis with different etiologies. Methods and result: during development of gel composition, natural semi-synthetic and synthetic gelatinizing agents have been used for gelatinization. In order to ensure required рН, ascorbic and lactic acids approved for medical use have been included into gel composition. Structural and mechanical properties have been investigated in experimental samples using a viscometer BROOKFIELD HB DV-2 PRO (USA). Determination of рН by potentiometric method using an ionometer (PH-150 MI) has been performed in accordance with the State Pharmacopoeia of Ukraine 1.2 . Conclusions. The introduction of ascorbic and lactic acids into gel composition at required concentrations leads to liquefaction of carbomer-based gels. Stability of gels is ensured by using xanthane gum at a concentration of 2-3% and hydroxyethyl cellulose at a concentration of 1-2%. As the result of the study the required concentration of lactic (0.1-0.2%) and ascorbic (3-4%) acids has been selected. Organoleptic, physical-chemical and rheological properties of the developed gels have been investigated.